Influência do inseticida Malathion sobre a mortalidade e a arquitetura branquial de camarões Macrobrachium amazonicum (HELLER, 1862) oriundos da bacia do rio Grande - ARDENGUI, Angelo Antonio Franzoi (2018)
Biota in aquatic ecosystems is usually exposed to various stress conditions, like natural environmental variations and anthropological disturbs including pollutant discharges into water resources. Malathion is an insecticide commonly used as an agricultural pesticide in crops around the world, and although it presents low toxicity to mammalian species, aquatic species may be sensitive even at small concentrations. Among the various aquatic organisms, crustaceans have distinguished themselves as sensitive organisms to evaluate the pollution of the aquatic ecosystem. In this sense, the objective of the present work was to evaluate the effects of malathion on Macrobrachium amazonicum shrimps by obtaining LD50 and morphological analysis of the gills. For this, native prawns of the Rio Grande were captured and acclimated to the laboratory environment for the realization of bioassays. The shrimp were divided into groups of ten animals each and exposed to increasing concentrations of the malathion for 48 hours. Our findings showed that the LD50 was reached at 0.73 mg/L malathion, and that relevant changes in the architecture of the gills can be observed in shrimps exposed to concentrations of 1.25 and 1.5 mg/L of the insecticide. This is the first report demonstrating that even in the short term, malathion interferes in the microscopic structure of Macrobrachium shrimp gills, and contributes to a better understanding of the effects promoted by certain pesticides on aquatic organisms that are commonly exposed to these.